The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1093/mnras/stz2481
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field, activity, and companions of V410 Tau

Abstract: We report the analysis, conducted as part of the MaTYSSE programme, of a spectropolarimetric monitoring of the ∼0.8 Myr, ∼1.4 M disc-less weak-line T Tauri star V410 Tau with the ESPaDOnS instrument at the Canada-France-Hawaii Telescope and NARVAL at the Télescope Bernard Lyot, between 2008 and 2016. With Zeeman-Doppler Imaging, we reconstruct the surface brightness and magnetic field of V410 Tau, and show that the star is heavily spotted and possesses a ∼550 G relatively toroidal magnetic field.We find that V… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
51
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(76 citation statements)
references
References 53 publications
20
51
5
Order By: Relevance
“…A polar spot extending at lower latitudes at phases 0.15 and 0.55 can, however, produce similar light curve characteristics. The cold spot configuration at the stellar surface of T Tauri stars is often found to be quite complex, consisting of several groups of spots (e.g., Yu et al 2019). Therefore, we can interpret the optical light curve variability as being due to two main spot groups at opposite longitudes or to an elongated polar spot with latitudinal extensions located at opposite azimuths at the time of our observations.…”
Section: Optical Photometrymentioning
confidence: 71%
“…A polar spot extending at lower latitudes at phases 0.15 and 0.55 can, however, produce similar light curve characteristics. The cold spot configuration at the stellar surface of T Tauri stars is often found to be quite complex, consisting of several groups of spots (e.g., Yu et al 2019). Therefore, we can interpret the optical light curve variability as being due to two main spot groups at opposite longitudes or to an elongated polar spot with latitudinal extensions located at opposite azimuths at the time of our observations.…”
Section: Optical Photometrymentioning
confidence: 71%
“…Our brightness modeling allows for bright surface patches as well, and the resulting map features a number of bright spots of relatively small area, with a specific concentration between latitudes 30 • and 45 • . The same set of techniques was also recently applied to the weak line T Tauri stars LkCa 4 (Donati et al 2014), V830 Tau (Donati et al 2016), TAP 26 (Yu et al 2017) and V410 Tau (Yu et al 2019). These four stars have masses relatively close to the one of V530 Per, although they all are significantly younger, and all rotate slower than V530 Per.…”
Section: Brightness Mapmentioning
confidence: 99%
“…The mean velocity of the Gaussian is the radial velocity. This is well adapted for slow rotators of K type such as HD 189733 (Pepe et al 2002;Bouchy et al 2005), but has been shown to prevent the recovery of RV information content for fast rotators (e.g., Galland et al 2005;Yu et al 2019) or M dwarfs in the optical (e.g., Astudillo-Defru et al 2015).…”
Section: Data Processingmentioning
confidence: 99%